Critical analysis of the human development index in Mesuji Regency, 2010–2022 - Suryanto, Sasmika Dwi; Mukhlis, Maulana; Makhya, Syarief; Rosalia, Feni (Annals of Human Resource Management Research, 2025)
Purpose: This study evaluates the performance of the Human Development Index (HDI) improvement program in the Mesuji Regency and identifies factors that influence the dynamics of HDI achievement. Mesuji is a peripheral region that experiences a significant socio-economic lag within Lampung Province, Indonesia. Research Methodology: This study employs a mixed method with an explanatory sequential design, combining quantitative analysis of HDI data from the BPS with qualitative interpretation of contextual and policy factors affecting HDI outcomes. Results: From 2010 to 2022, Mesuji’s HDI steadily increased, driven by improvements in Life Expectancy, Education Index, and Gross National Income per Capita. Key drivers include improved healthcare services, educational expansion, job availability, infrastructure development, and pro-poverty policies. Conclusions: The program aimed at increasing the Human Development Index (HDI) in Mesuji Regency has shown positive results from 2010 to 2022, yet the region's HDI remains classified as "medium" compared to the national average. Limitations: The analysis was limited to the 2010–2022 period, excluding developments beyond this range. Contribution: This study contributes to challenges such as regional development disparities, high poverty rates, and unemployment, which still need to be addressed to achieve more equitable and sustainable development. Novelty: Despite positive growth, Mesuji’s HDI remains in the “medium” category, highlighting the need for strategic and sustained efforts in the health, education, and income sectors. Comprehensive interventions supported by inclusive policies are essential to accelerate HDI progress and reduce regional disparities.